The Impact of Hypoxemia on Nephropathy in Extremely Obese Patients with Type 2 Diabetes Mellitus - Leong, Wen Bun (American Academy of Sleep Medicine, 2014)
STUDY OBJECTIVES: Diabetes mellitus (DM) is associated with obstructive sleep apnea (OSA) and nephropathy. The hypoxemia associated with OSA may exacerbate renal deterioration in DM nephropathy. We examined the role of hypoxemia in the development of DM nephropathy in severely obese patients. METHODS: This cross-sectional study examined anonymized data from 90 DM patients with extreme obesity attending a weight management service. All patients underwent a routine overnight sleep study. Respiratory parameters measured included apnea-hypopnea index (AHI), mean and minimum oxygen (O(2)) saturations, and time spent under 90% O(2) saturation (%TST < 90%). Chronic kidney disease (CKD+) was defined as estimated glomerular filtration rate (eGFR) ≤ 60 mL/min/1.73 m(2). RESULTS: Twenty (22%) patients were CKD+. These patients were 7 years older (mean age ± SD 57 ± 11 years, p = 0.003) and had greater adiposity (mean body mass index [BMI] ± SD 50.6 ± 8.7 kg/m(2), p = 0.012). No significant differences were found for median AHI and minimum O(2) saturation. %TST < 90% was 4 times greater in CKD+ group (p = 0.046). Multivariate regression analysis showed that AHI (β = −0.17, 95% CI: −0.316 to −0.024) and %TST < 90% (β = −0.215, 95% CI: −0.406 to −0.023) were negatively correlated with eGFR after adjustment for age, gender, BMI, comorbidities, insulin treatment, and drugs affecting the renin-angiotensin system. No associations were found between mean and minimum O(2) saturations, and eGFR. CONCLUSION: Apnea and hypopnea events as well as duration of nocturnal hypoxemia were inversely associated with renal function after adjusting for potential confounders. Given the significant burden of renal disease in diabetes, greater vigilance is required in identifying OSA in DM patients with extreme obesity. CITATION: Leong WB, Nolen M, Thomas GN, Adab P, Banerjee D, Taheri S. The impact of hypoxemia on nephropathy in extremely obese patients with type 2 diabetes mellitus. J Clin Sleep Med 2014;10(7):773-778.